To kill a mockingbird - Pakula, Alan; Mulligan, Robert; Foot, Horton (MGM Home Video, 1987)
SUMMARY: Two children in a small southern town are thrust into an adult world of racial bigotry and hatred when their father chooses to defend a black man charged with raping a white girl.